Cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC) for chronic insomnia disorder ('CANSLEEP' trial): protocol for a randomised, placebo-controlled, double-blinded, proof-of-concept trial. Issue 5 (18th May 2020) - Suraev, Anastasia; Grunstein, Ronald R; Marshall, Nathaniel S; D'Rozario, Angela L; Gordon, Christopher J; Bartlett, Delwyn J; Wong, Keith; Yee, Brendon J; Vandrey, Ryan; Irwin, Chris; Arnold, Jonathon C; McGregor, Iain S; et al.
Abstract : Introduction: Insomnia is a highly prevalent and costly condition that is associated with increased health risks and healthcare utilisation. Anecdotally, cannabis use is frequently reported by consumers to promote sleep. However, there is limited research on the effects of cannabis on sleep and daytime function in people with insomnia disorder using objective measures. This proof-of-concept study will evaluate the effects of a single dose of an oral cannabis-based medicine on sleep and daytime function in participants with chronic insomnia disorder. Methods and analysis: A randomised, crossover, placebo-controlled, single-dose study design will be used to test the safety and efficacy of an oral oil solution ('ETC120') containing 10 mg Δ 9 -tetrahydrocannabinol (THC) and 200 mg cannabidiol (CBD) in 20 participants diagnosed with chronic insomnia disorder. Participants aged 35–60 years will be recruited over an 18-month period commencing August 2019. Each participant will receive both the active drug and matched placebo, in a counterbalanced order, during two overnight study assessment visits, with at least a 1-week washout period between each visit. The primary outcomes are total sleep time and wake after sleep onset assessed via polysomnography. In addition, 256-channel high-density electroencephalography and source modelling using structural brain MRI will be used to comprehensively examine brain activation during sleep and wake periods on ETC120 versus placebo. Next-day cognitive function, alertness and simulated driving performance will also be investigated. Ethics and dissemination: Ethics approval was received from Bellberry Human Research Ethics Committee (2018-04-284). The findings will be disseminated in a peer-reviewed open-access journal and at academic conferences. Trial registration number: ANZCTRN12619000714189.